Perubahan Pengetahuan, Pola Konsumsi, Asupan Gizi, dan Food acculturation Mahasiswa Baru Perantau dan Nonrantau: Penelitian Kohort 5 Bulan - Anuz, Amany Ges; Mahmudiono, Trias (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
This study examines changes in nutritional knowledge, dietary patterns, nutrient intake, and food acculturation among first-year migrant and non-migrant students. A 5 months prospective cohort design was employed involving 32 students from the Faculty of Public Health, Universitas Airlangga. Students were randomly divided equally into migrant and non-migrant groups. Data were collected using questionnaires, food frequency questionnaires, 3×24-hour food recall, and analyzed using descriptive and inferential statistics. The findings indicated no significant differences or changes in nutritional knowledge between groups throughout the observation period (p > 0.05). However, dietary patterns varied, with migrant students showing increased consumption of practical and fast foods. Nutrient intake, particularly energy and protein, was initially lower among migrant students but improved significantly over time, reflecting adaptation to a new environment. Food acculturation was evident among migrant students, with a significant increase in scores during the study period (p = 0.007), indicating gradual adjustment to local eating habits. These results highlight the influence of environmental adaptation on students’ dietary behavior and emphasize the need for targeted nutrition interventions to promote healthy eating habits during the early university transition.